Neuronal mitochondria-targeted therapy for Alzheimer's disease by systemic delivery of resveratrol using dual-modified novel biomimetic nanosystems - Yang Han; Xiaoyang Chu; Lin Cui; Shiyao Fu; Chunsheng Gao; Yi Li; Baoshan Sun (Taylor & Francis Group, 2020)
Reactive oxygen species (ROS)-induced neuronal mitochondrial dysfunction is a key pathologic factor in sporadic Alzheimer's disease (AD). Neuronal mitochondria have been proposed to be a promising therapeutic target for AD, especially for the failures of phase III clinical trials on conventional amyloid-β (Aβ) targeted therapy. However, the efficient intravenous delivery of therapeutic agents to neuronal mitochondria in the brain remains a major challenge due to the complicated physiological environment. Recently, biomaterials-based nanomedicine has been widely investigated for the treatment of AD. Herein, we devised a strategy for functional antioxidant delivery to neuronal mitochondria by loading antioxidants into red blood cell (RBC) membrane-coated nanostructured lipid carriers (NLC) bearing rabies virus glycoprotein (RVG29) and triphenylphosphine cation (TPP) molecules attached to the RBC membrane surface (RVG/TPP NPs@RBCm). With the advantage of suitable physicochemical properties of NLC and unique biological functions of the RBC membrane, RVG/TPP NPs@RBCm are stabilized and enabled sustained drug release, providing improved biocompatibility and long-term circulation. Under the synergistic effects of RVG29 and TPP, RVG/TPP NPs@RBCm can not only penetrate the blood-brain barrier (BBB) but also target neuron cells and further localize in the mitochondria. After encapsulating Resveratrol (RSV) as the model antioxidant, the data demonstrated that RVG/TPP-RSV NPs@RBCm can relieve AD symptoms by mitigating Aβ-related mitochondrial oxidative stress both in vitro and in vivo. The memory impairment in APP/PS1 mice is significantly improved following the systemic administration of RVG/TPP-RSV NPs@RBCm. In conclusion, intravenous neuronal mitochondria-targeted dual-modified novel biomimetic nanosystems are a promising therapeutic candidate for ROS-induced mitochondrial dysfunction in AD.